The influence of fiqh insights and science literacy on student ability in developing Quran-based science - Muhammad Umar; Sukarno Sukarno (Institute of Advanced Engineering and Science, 2022)
Islamic education institutions are responsible for the process of integration of knowledge which aims to encourage the mastery and improvement of general science and religious knowledge in harmony. This study aimed to see the extent of the influence of the ability of fiqh (Islamic jurisprudence) and scientific literacy on the ability of physics students in developing integrated learning Quran-based science. Through a quantitative approach with a survey model of physics education students involving 150 students, it was found that the correlation value Rcal (0.943)>Rtable (0.1339) with a sig. value (2-tailed) 0.000<0.05. Furthermore, it is also known that the correlation between scientific literacy and integration ability is Rcal (0.512)>Rtable (0.1339) with a sig. (2-tailed) 0.000<0.05. ANOVA test results (F test) showed the value of Fcal (632.126)>F table 3.91 with a probability of 0.05. Thus, it can be understood that simultaneously the independent variables (fiqh insights and scientific literacy) affect the dependent variable (the ability to develop integrated learning Quran-based science as tools of learning). These results are also supported by a sig. 0.00<0.05, which means that the independent variables simultaneously influence the dependent variable significantly.